2019
DOI: 10.1002/chem.201903022
|View full text |Cite
|
Sign up to set email alerts
|

Directed Nanoparticle Assembly through Polymer Crystallization

Abstract: Nanoparticles can be assembled into complex structures and architectures by using a variety of methods. In this review, we discuss recent progress of using polymer crystallization (particularly polymer single crystals, PSCs) to direct nanoparticle assembly. PSCs have been extensively studied since 1957. Mainly appearing as quasi‐two‐dimensional (2D) lamellae, PSCs are typically used as model systems to determine polymer crystalline structures, or as markers to investigate the crystallization process. Recent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 139 publications
0
22
0
Order By: Relevance
“…It has previously been demonstrated that functional polymer chain ends can be expressed on the surface of polymer crystals and similarly that dyes can be incorporated onto the surface of crystalline-core BCP NPs through the co-assembly of dye labelled and unlabelled crystallisable homopolymers. 56,57 To achieve a similar result we synthesised a P i PrOx homopolymer end-functionalised with Cy5 (P i PrOx 40 -Cy5, Fig. S3 † ) as shown in Scheme S1.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that functional polymer chain ends can be expressed on the surface of polymer crystals and similarly that dyes can be incorporated onto the surface of crystalline-core BCP NPs through the co-assembly of dye labelled and unlabelled crystallisable homopolymers. 56,57 To achieve a similar result we synthesised a P i PrOx homopolymer end-functionalised with Cy5 (P i PrOx 40 -Cy5, Fig. S3 † ) as shown in Scheme S1.…”
Section: Resultsmentioning
confidence: 99%
“…The emission yield of these materials can be enhanced for potential applications in imaging, sensing, diagnosis, and therapy, but remains to be explored to its full extent . However, other nanostructures have been widely used for these applications, either due to their unique properties or due to their chemically controlled architectonics . GNRs can efficiently convert absorbed light into heat either through electron–electron interactions or electron–phonon interactions and have been established for their photothermal therapy (PTT) efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] However, other nanostructures have been widely used for these applications, either due to their uniquep roperties or due to their chemically controlled architectonics. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] GNRs can efficiently convert absorbed light into heat either through electron-electron interactions or electron-phonon interactions and have been established for their photothermal therapy (PTT) efficacy. [30,31] Furthermore, by incorporating ap hotosensitizer (PS) molecule, with ah igh singleto xygen yield, additional treatment modality,s uch as photodynamic therapy (PDT) could also be enabled in the same system, in addition to PTT.…”
Section: Introductionmentioning
confidence: 99%
“…Being widely commercially available, PCL has a high capacity to be miscibly blended, and this has resulted in interesting compatibilization studies [ 22 , 23 , 24 ]. Whether in blends or copolymers of various architectures [ 25 , 26 , 27 ], PCL is easily shaped and manufactured in the form of hydrogels [ 22 , 23 ], nanoparticles [ 24 ], nanofibers [ 27 , 28 ], and, more importantly, due to its crystallizable nature, into a well-defined and geometrically shaped 2D lamellar single-crystal structure that has various and interesting applications [ 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, innovative uses of ε-caprolactone-based segments in sophisticated polymer architectures or micellar systems have also been noted [ 21 ]. Thus, the end-group functionalization of PCL means that it can be applied in, for example, more efficient drug delivery systems [ 5 , 11 ] and in aggregation-induced emission (AIE) materials [ 7 ], as catalytically active recyclable materials, or as magnetically responsive, luminescent materials [ 29 ]. Moreover, functional groups have often been added to PCL to transform it into a reactive intermediate in order to subsequently use them in coupling reactions.…”
Section: Introductionmentioning
confidence: 99%